2020
DOI: 10.3390/en13205274
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Fire Analysis of Gob Characteristics Using CFD

Abstract: A laboratory-scale analysis using coal from an underground mine was carried out, emulating a mixture from the gob area in an actual mine, consisting of waste, coal, and free space for the flow of air. Experimental tests and computational fluid dynamics modelling were done to define and verify the behavior of the collapsed region in a time-dependent analysis. In addition, the characteristics of coal were defined, regarding the self-combustion, combustion rate, and pollutants generated in each stage of the fire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Recently, there has been a rising interest in providing fire systems that can provide reliable early detection of fires [1]. However, most conventional studies of fire science are based on numerical experiments such as CFD simulations [2][3][4] and not on actual experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a rising interest in providing fire systems that can provide reliable early detection of fires [1]. However, most conventional studies of fire science are based on numerical experiments such as CFD simulations [2][3][4] and not on actual experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…• A section of the tailgate with an assumed length of 30 m and a 20 m liquidated section with the characteristics of the goaf area with a cross-section of 15.2 m 2 ; • Longwall excavation 25 m long, 3 m high, 8 m wide and with an inclination of 0 o , the floor of the longwall was 1 m below the floor of the tailgate. This was due to the uplift of the tailgate floor as a result of a high-stress concentration; • A section of goafs with an assumed length of 20 m, a height equal to the height of the longwall and a width of 25 m, modeled as a porous medium [33][34][35] (based on tests, it was shown that it is reasonable to assume the height of the goafs to be equal to the height of the longwall); • A 10 m long brattice, located 4 m from the cave line in the tailgate; • An auxiliary air-duct, 21 m long and diameter of 1 m, located 0.9 m from the excavation floor, with an outlet located 0.5 m from the longwall; • A zone filled with sealing foam material from the side of goafs in the liquidated part of the tailgate.…”
Section: Methodsmentioning
confidence: 99%
“…9., 13., presents air velocity distribution along excavation length, Figures 6.,10., and 14. velocity distribution in the cross-sections of the excavation every two meters of its length, while Figures 12., 8., and 16. presents the normal distribution of air velocity considering the turbulence models applied. This section has been supported additionally with the graphs representing average air velocity values in given crosssections obtained for the chosen turbulence models presented inFigures 7.,11.,and 15. …”
mentioning
confidence: 88%
“…Numerical modeling is also used to eliminate and prevent fires in underground workings by planning the removal of gases resulting from combustion. Proper planning of the method and strength of ventilation can quickly remove harmful gases from the fire site without spreading them to adjacent tunnels [8,9,10,11].…”
Section: State Of the Artmentioning
confidence: 99%